Mid-infrared supercontinuum generation using As2Se3 photonic crystal fiber and the impact of higher-order dispersion parameters on its supercontinuum bandwidth - Karim, Mohammad Rezaul; Ahmad, Harith; Ghosh, Souvik; Rahman, B.M. Azizur (Elsevier, 2018)
A dispersion engineered As2Se3 chalcogenide hexagonal photonic crystal fiber which can produce a mid-infrared supercontinuum (SC) spectral evolution spanning from 2 μm to beyond 15 μm with a low peak power of 3 kW is numerically designed and demonstrated. Numerical analysis is carried out to investigate the impact of higher-order dispersion (HOD) parameters on the output SC bandwidth and shows that the SC spectral broadening at the output of the proposed design depends on the convergence of the Taylor approximation with increasing fitting parameters, which implies a sufficient number of HOD parameters must be included during numerical simulations. Four designs with different structural parameters are optimized for pumping, each operating at a different pump wavelength to test the convergence of output SC by the successive addition of HOD parameters. To realize spurious free SC spectral evolution by the proposed designs, HOD terms up to the sixteenth-order are included during all SC simulations. The proposed design can be used in molecular finger print spectroscopy, bio-medical imaging as well as various mid-infrared region applications.